Azolla and vermicomposta: Semblance of the life and work of Dr. Roberto Quintero Lizaola - Espinosa Victoria, David; Rentería Chávez, Ma. Concepción (REVISTA TERRA LATINOAMERICANA, 2019)
The present review is a symbolic post-mortem tribute that the Mexican Society of Soil Science (MSSS) C.A. pays to the memory of Dr. Roberto Quintero Lizaola. Dr. Quintero Lizaola was born in Ameca, Jalisco, Mexico, on May 5, 1958 and died on August 22, 2018 in the City of Texcoco, State of Mexico. During his scientific life, Dr. Quintero Lizaola distinguished himself as an active militant of the MSSS, C.A. In addition to participating as a speaker and coordinator of working groups in different conferences, he was involved in different committees for the benefit of the MSSS, AC. He served as general secretary of the MSSS, C.A. of 1991-1995. Likewise, he participated as a member of the Action Committee for Environmental Sanitation (ACES), C.A. Dr. Quintero Lizaola focused his research on the study and application of the Azolla aquatic fern, as well as on the characterization and use of vermicomposts. His legacy as soil researcher is reflected in the annals of the MSSS, C.A.